2009
DOI: 10.1038/nrn2538
|View full text |Cite|
|
Sign up to set email alerts
|

Conflict-induced behavioural adjustment: a clue to the executive functions of the prefrontal cortex

Abstract: The behavioural adjustment that follows the experience of conflict has been extensively studied in humans, leading to influential models of executive-control adjustment. Recent studies have revealed striking similarities in conflict-induced behavioural adjustment between humans and monkeys, indicating that monkeys can provide a model to study the underlying neural substrates and mechanisms of such behaviour. These studies have advanced our knowledge about the role of different prefrontal brain regions, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
428
2
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 504 publications
(457 citation statements)
references
References 94 publications
24
428
2
3
Order By: Relevance
“…The frontal lobe, especially the prefrontal cortex (PFC) plays an essential role in various high‐level cognitive functions, such as executive functions (Mansouri, Tanaka, & Buckley, 2009; Miller, 2000; Miller & Cohen, 2001), reasoning and planning (Wood & Grafman, 2003), decision making (Wallis, 2007), social cognition, and moral judgment (Forbes & Grafman, 2010). Meanwhile, the deficits in PFC functions are involved in the pathophysiology of several psychiatric and neurological disorders such as schizophrenia, drug addiction, mood disorders, and Alzheimer's disease (Fuster, 2001; Goto, Yang, & Otani, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The frontal lobe, especially the prefrontal cortex (PFC) plays an essential role in various high‐level cognitive functions, such as executive functions (Mansouri, Tanaka, & Buckley, 2009; Miller, 2000; Miller & Cohen, 2001), reasoning and planning (Wood & Grafman, 2003), decision making (Wallis, 2007), social cognition, and moral judgment (Forbes & Grafman, 2010). Meanwhile, the deficits in PFC functions are involved in the pathophysiology of several psychiatric and neurological disorders such as schizophrenia, drug addiction, mood disorders, and Alzheimer's disease (Fuster, 2001; Goto, Yang, & Otani, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, other studies have found right inferior frontal gyrus activation in the explicit condition (Bach et al, 2008;Ethofer et al, 2009). Overall, the inferior frontal gyrus and the other frontal clusters activated during implicit processing of musical emotions belong to the dorsolateral prefrontal cortex (DLPFC), which is generally involved in working memory (Smith & Jonides, 1999), response selection (Bunge et al, 2002), and rule-guided behavior (Mansouri et al, 2009), but also in conscious emotion regulation (Kohn et al, 2014), and has been observed in response to music emotions (Khalfa et al, 2005). Indeed, the neighboring activity in premotor areas of the frontal gyrus is commonly observed in response to music-induced emotions (Blood & Zatorre, 2001;Mitterschiffthaler et al, 2007;Mizuno & Sugishita, 2007).…”
Section: Implicit Vs Explicit Processingmentioning
confidence: 99%
“…Moreover, the DLPFC maintains and updates comprehensive representations of the task context by encoding task relevant rules and associated responses, stimulus features and conflict (Mansouri, Tanaka, & Buckley, 2009). …”
Section: Introductionmentioning
confidence: 99%